2011
DOI: 10.1159/000327947
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Collagen XVI Expression Reduces Glioma Cell Invasiveness

Abstract: Glioblastomas are characterized by an intense local invasiveness that limits surgical resection. One mechanism by which glioma cells enforce their migration into brain tissue is reorganization of tumour associated extracellular matrix (ECM). Collagen XVI is a minor component of connective tissues. However, in glioblastoma tissue it is dramatically upregulated compared to the ECM of normal cortex. The aim of this study is to delineate tumour cell invasion and underlying mechanisms involving collagen XVI by usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…These levels were elevated in 60% of lung and 70% of colon cancers 57 . Kindlin-1 was also found to be associated with the pathology of glioma 58 . Kindlin-1 mRNA also was highly expressed in the pancreatic cancer cell lines and pancreatic cancer tissue 59 .…”
Section: Association Of Kindlins With Cancermentioning
confidence: 92%
“…These levels were elevated in 60% of lung and 70% of colon cancers 57 . Kindlin-1 was also found to be associated with the pathology of glioma 58 . Kindlin-1 mRNA also was highly expressed in the pancreatic cancer cell lines and pancreatic cancer tissue 59 .…”
Section: Association Of Kindlins With Cancermentioning
confidence: 92%
“…In normal oral epithelium as in the dermis, collagen XVI is predominantly located at the dermal-epidermal junction [8], [16]. Collagen XVI is involved in dermal architecture by interacting with integrins alpha1beta1, alpha2beta1 and the microfibrillar apparatus [8], [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is not only produced by dermal fibroblasts but also by smooth muscle cells [9], dermal dendrocytes [10], articular and costal chondrocytes [7], endometrial stromal cells [11], basal dermal and oral keratinocytes [8], [12], [15], neurons from the dorsal root ganglion [13] and glioblastoma / astrocytoma cells [14]. Recent studies have shown, that collagen XVI is implicated in the development of glioblastoma and OSCC, in which it is overexpressed during tumor progression and influences cell cycle progression [12], [14][16].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of several extracellular matrix and collagen genes has been related to invasion and survival in some other tumors. [47][48][49] The recognition of a desmoplastic response to cancer has long been recognized, [50][51][52] and the role of tumor-associated fibroblasts in the growth and development of cancer is a topic of recent research. 36,46,[53][54][55][56] The use of the AF gene set in the current study raises the question of the contribution of the stroma to the gene expression pattern and biology of the tumor.…”
Section: Discussionmentioning
confidence: 99%